2011
DOI: 10.1177/1534650111420706
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Immigrants Presenting With Social Anxiety Disorder

Abstract: Cognitive-behavioral therapy (CBT) for the treatment of Social Anxiety Disorder (SAD) has demonstrated efficacy in numerous randomized trials. However, few studies specifically examine the applicability of such treatment for ethnic minority clients. Thus, the purpose of this article is to present two case studies examining the utility of individualized CBT for SAD with two clients who immigrated to the United States, one from Central America and one from China, for whom English was not their primary language. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Two of the reviewed cases emphasized the role of native languages in therapy (Weiss et al ., 2011) and indicated that much more consideration needs to be given to the utilization of native languages in CBT. Clients who do not have English as their first language may find it difficult to access their thoughts or the thoughts can be ‘lost in translation’, making cognitive work less beneficial.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the reviewed cases emphasized the role of native languages in therapy (Weiss et al ., 2011) and indicated that much more consideration needs to be given to the utilization of native languages in CBT. Clients who do not have English as their first language may find it difficult to access their thoughts or the thoughts can be ‘lost in translation’, making cognitive work less beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…Weiss et al . (2011) advocate the incorporation of native language in CBT, especially in written homework assignments, such as thought records. Yet, asking clients to express themselves in their native languages needs to be introduced carefully, not to give them an impression that a therapist perceives them as unable to speak the language of the dominant culture, as this may perpetuate their fear of social judgement and/or distorted perception of their language proficiency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations